Double-bond-containing polyallene-based composite nanofibers. (June 2022) - Yuan, Zongqian; Ding, Aishun; Xu, Binbin; Huang, Xiaoyu; Lu, Guolin; Guo, Hao
Abstract: Composite nanofibers have attracted increasing attention due to their applications in a variety of fields, such as biomedicine, nanoelectronic and drug delivery systems. Particularly, the introduction of customizable reactive segments to composite nanofibers is proven efficient to generate novel nanomaterials with extra functionalities. However, the preparation of reactive composite nanofibers unavoidably involves multiple-step and tedious manipulations. In addition, these nanofibers are generally prepared at high dilution, which restricts their potential applications. Herein, a new method of producing reactive composite nanofibers was reported through the polymerization-induced self-assembly (PISA) formulation of poly(phenoxyallene) (PPOA)-containing diblock copolymers. Reversible addition-fragmentation chain transfer (RAFT) block copolymerization of styrene and POA was chosen as a model reaction to explore the polymerization and PISA conditions. It was found that a chain transfer agent (CTA) consisting of C12 H25 S as Z segment and –COOH in R moiety allows for the preparation of well-defined double-bond-containing poly(styrene)- b -poly(phenoxyallene) (PS- b -PPOA), poly(methyl acrylate)- b -poly(phenoxyallene) (PMA- b -PPOA) and poly(methyl methacrylate)- b -poly(phenoxyallene) (PMMA- b -PPOA) diblock copolymers with controlled molecular weights and narrow dispersities. Specifically, on the basis of as-prepared poly(ethylene glycol) (PEG) macro-CTA, we demonstrated the in situ formation of unique composite nanoﬁbers of PEG- b -PPOA via PISA process in methanol. Our work provides a facile synthetic approach toward attractive one-dimensional composite nanofibers with controlled dimension and a capacity for post-functionalization. Graphical abstract: Image 1 Highlights: Well-defined reactive poly(phenoxyallene) (PPOA)-containing diblock copolymers were prepared. The in situ formation of unique nanoﬁbers of poly(ethylene glycol)- b -poly(phenoxyallene) (PEG- b -PPOA) via a PISA process. The morphology transformation of aggregates from the spherical micelles to fibers.